Changing Mechanisms of High-Temperature Oxidation of Zr-1%Nb Alloy in Air and Steam by Surface Modification with Charged Particles; Journal of Materials Engineering and Performance; Vol. 34, iss. 13 - Slobodyan M. S. Mikhail Stepanovich; Ivanov K. A. Konstantin Aleksandrovich; Klimenov V. A. Vasily Aleksandrovich; Strelkova I. L. Irina Leonidovna; Tarbokov V. A. Vladislav Aleksandrovich; Pavlov S. K. Sergey Konstantinovich; Remnev (Remnyov) G. E. Gennady Efimovich; Yolkin M. Maksim; Uglov V. V. Vladimir Vasiljevich (2025, 2025)
Title screen